Category of Directed Complete L-slices - Sabna, K.S.; Mangalambal, N.R. (Sarajevo Journal of Mathematics, 2025)
A new notion of action of a locale $ L $ on $ P $ is developed in the context of point free topology, given a locale $ L $ and a directed complete join semilattice $ P $ with bottom element $ 0_{P} $. This work establishes the existence of a contravariant functor from the category TopDWMod of topological directed weak L-modules and continuous weak L-module homomorphisms to the category DL-slice of directed complete L-slices and directed complete L-slice homomorphisms.